Overexpression of SoCYP85A1, a Spinach Cytochrome p450 Gene in Transgenic Tobacco Enhances Root Development and Drought Stress Tolerance - Duan, Fangmeng; Ding, Jun; Lee, Dongsun; Lu, Xueli; Feng, Yuqi; Song, Wenwen (Frontiers in Plant Science, 2017)
Brassinosteroids (BRs) play an essential role in plant growth, development and responses to diverse abiotic stresses. However, previous studies mainly analyzed how exogenous BRs influenced plant physiological reactions to drought stress, therefore, genetic evidences for the endogenous BRs-mediated regulation of plant responses still remain elusive. In this study, a key BRs biosynthetic gene, SoCYP85A1 was cloned from Spinacia oleracea, which has a complete open reading frame of 1392 bp encoding a 464 amino acid peptide and shares high sequence similarities with CYP85A1 from other plants. The expression of SoCYP85A1 which was higher in leaf compared with root and stem, was induced by treatments of PEG6000, ABA, low temperature and high salt. Increases in both SoCYP85A1 transcripts and endogenous BRs in transgenic tobacco which resulted in longer primary root and more lateral roots enhanced drought tolerance compared with wild types. The transgenic tobacco accumulated much lower levels of reactive oxygen species and MDA than wild types did, accompanied by significantly higher content of proline and notably enhanced activities of antioxidant enzymes. Besides, transcriptional expressions of six stress-responsive genes were regulated to higher levels in transgenic lines under drought stress. Taken together, our results demonstrated that SoCYP85A1 involves in response to drought stress by promoting root development, scavenging ROS and regulating expressions of stress-responsive genes.